Estimasi Harga Pokok Produksi Roll Gilingan Dengan Metode Job Order Costing Dalam Penentuan Harga Jual (Studi Kasus Pada Perusahaan Manufaktur Khususnya Workshop 4) - Regita Palupi; Rina Sandora; RA. Norromadani Yuniati (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The manufacturing company located in Gresik is one of the companies that produce roll mill. Roll mill is a sugar plant equipment used for squeezing cane. In the calculation of cost of goods manufactured, the company does not include fixed overhead costs into the calculation of the cost of production. The calculation will be more accurate and detailed if the company uses job order costing method of full costing approach. The full costing approach calculates direct raw materials, direct labor, factory overhead costs, both variable and fixed. One example is PG.Pagotan orders where the results using JOC with full costing approach is Rp466.687.630,- for cost of goods manufactured, Rp93.337526,- for profit and Rp616.027.672,- for sale price. While the result set by the company is Rp438.625.790,- for the cost of goods manufactured, Rp87.725.158,- for profit and Rp578.986.000,- for the sale price. The result using JOC with full costing approach is greater than that of the firm of this difference due to differences in the way grouping and incremental costs are incorporated into cost of goods manufactured calculations using the full cost JOC method. Cost of goods manufactured calculated on the basis of the company is undercosting. The test results of 22 orders with the t test get the value of Sig. (2-tailed) = 0.00 <0.05 so it shows a significant difference between the value of cost of goods manufactured, the profit and the selling price set by the company with the value using the JOC approach full method costing.